Hot embossing and injection molding of three-dimensional microcomponents - Ali, Mohammad Yeakub; Ngoi, B. K. A.; Hung, N. P.; Yuan, S.; Lee, C.P. (2001)
This paper discusses hot embossing and injection molding microreplication processes for the fabrication of three dimensional (3D) microcomponents. These techniques included specialized tooling and variothermal process control. The microcavities were fabricated by focused ion beam (FIB) sputtering. Microgears, microgear trains, microlenses etc. were successfully replicated from polymers. The overall size of these microcomponents were few tens to few hundred micrometers. These replicated microcomponents were inspected with scanning electron microscope where submicrometer accuracy and faithful replication of cavity surface texture were observed.